Scaredy Squirrel gets a surprise - Watt, Mélanie, 1975- (Watt, Mélanie, 1975- Scaredy's nutty adventures, 2022)
Scaredy Squirrel opens a mysterious crate containing a pool and as his friends try to help him enjoy the pool, Scaredy Squirrel learns that not all surprises are bad.